Interchangeability of Natural Gas Quality Indicators as Fuel for Gas Turbine Performance of Power Generation - Seham N. Tawfic; Ibrahim M. Abou El Leil (African Journal of Advanced Pure and Applied Sciences, 2024)
Today’s highly efficient gas turbines relies on the quality of the fuel utilized. Where, high-quality fuel permits achieving high combustion temperatures, thereby achieving an acceptable level of produced energy. Therefore, more attention has to be placed on the quality of the fuel, from all sources, entering the gas turbine. Consequently, the characterizations and quality parameters of natural gas mixtures must be investigated to determine their specifications. This study highlights the natural gases that produced from Zelten, Al Ragoba and Al Hotaiba gas fields of Sirte Oil Company aiming to assess the quality indicators as a fuel for turbines of power generation and provides an insight as well as understanding of fuel composition so that measures can be taken to minimize the impact of any major constituents of the fuel, along with the potential impact on turbine components. These parameters are gas molecular weight ( ), specific gravity , compressibility factor (z), pseudocritical pressure ( ), pseudocritical temperature ( ), pseudoreduced pressure ( ) and pseudoreduced temperature ( ) to estimate the quality indicators such as gross heating value (GHV), Wobbe index (WI), methane number (MN) and calorific values (CV). The obtained results revealed that there are a variance between these parameters of the natural gas mixtures, which may be attributed to the chemical compositions of components and their behaviors. On the other hand, these characterizations can be used as guide to understand the gases behavior as a fuel for combustion processes in gas turbines. In general, the quality parameters indicate that the specifications and characterizations within the required limits for natural gases quality and can be utilized as a fuel for turbine in power generation.